If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(9x + 5) = 190 Reorder the terms: 2(5 + 9x) = 190 (5 * 2 + 9x * 2) = 190 (10 + 18x) = 190 Solving 10 + 18x = 190 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 18x = 190 + -10 Combine like terms: 10 + -10 = 0 0 + 18x = 190 + -10 18x = 190 + -10 Combine like terms: 190 + -10 = 180 18x = 180 Divide each side by '18'. x = 10 Simplifying x = 10
| x^2-15x-44=7x+4 | | x^2+x-38=9x-5 | | 5x+2=x+3.6 | | x^2+11x+31=1 | | 5x=8y+1 | | -7x-1.6=-5-1.2 | | 8m-0=16 | | 4(6x-9)=180 | | -7.4-2.4=-6x-2.9 | | U=5(2W-4W^3+5W^2) | | 6x+5=2x+65 | | 4/7*135 | | 3/64*4 | | 12x-228=3x-12 | | 9y-9=1 | | X^2+16-58=0 | | 1.3=26p | | 6x^2-5x+4h=0 | | 2(-3/2)-1 | | x^14-81=0 | | 7x-9=x+4 | | X-x/8-x | | -2y-15y=23 | | 4x+2x-6=4(x-3)+7 | | 2x-1/4x=4/6 | | 3b^2-7b-2=0 | | (5z+2)(6-z)=0 | | X/2-1/4=20 | | y-9=55 | | 13+x-7=-2-3x | | (5x-12)+2x=20+x | | (2x+8)(3x-2)= |